Wind Load Characterization Considering Three Container Cranes in Array Arrangement - Dazhi Huang; Yusheng Su; Qing Wang; Zetan Gu; Jiaqi Cheng; Zhiyu Wei (IEEE Access, 2024)
This study focuses on the wind characteristics of three container cranes discharged side-by-side under wind loads. Three-dimensional models of the three container cranes were established using Computational Fluid Dynamics (CFD). The wind load pattern among the three container cranes was studied by adjusting parameters such as the positional state of the arm of the container cranes, the wind angle, and the spacing of the container cranes. The results show that the maximum wind load borne by container cranes occurs at a 45° wind angle. At a wind angle of 90°, the wind resistance effect was optimal when the spacing between the three container cranes was 45 m. Wind reduction was approximately 63% in the boom-up state of the container cranes and 58% in the boom-down state of the arm. In addition, the study found that the critical spacing of the container cranes was 75 m in the boom-down state of the arm. When the distance between container cranes was greater than 75 m, the wind resistance effect between the container cranes gradually decreased until it disappeared. In the boom-up state of the arm, the critical spacing of the container cranes is 60 m. When the spacing between container cranes was greater than 60 m, the change in the wind resistance coefficient decreased.